Analisis Profil Asam Lemak Minyak Zaitun (Olea Europaea L.) Menggunakan Metode GC-MS dan FT-IR - Nur Aeni; Andi Eka Kartika (Jurnal Inovasi Teknik Kimia, 2026)
Olive oil (Olea europaea L.) is a high-value vegetable oil rich in unsaturated fatty acids and bioactive compounds beneficial to health. However, variability in quality and the risk of adulteration require accurate chemical characterization. This study aims to analyze the fatty acid profile and chemical characteristics of olive oil using a combination of Gas Chromatography–Mass Spectrometry (GC–MS) and Fourier Transform Infrared Spectroscopy (FT–IR). Olive oil samples were analyzed before and after 12 hours of ultrasonic treatment, preceded by a methylation process to form fatty acid methyl esters. GC–MS was used to identify fatty acid components based on retention time and mass spectra, while FT–IR was employed to observe the main functional groups of triglycerides. The GC–MS results showed oleic acid as the dominant component, increasing from 58.36% before to 68.59% after ultrasonic treatment, followed by palmitic and linoleic acids. FT–IR spectra exhibited characteristic peaks at ~2924 cm⁻¹, 1745 cm⁻¹, and 1163 cm⁻¹, confirming the triglyceride structure. The combination of GC–MS and FT–IR proved effective for evaluating the quality and authenticity of olive oil.